Chronic exposure to the ionic liquid [C8mim]Br induces inflammation in silver carp spleen: Involvement of oxidative stress-mediated p38MAPK/NF-κB signalling and microRNAs. Issue 84 (January 2019) - Ma, Junguo; Chen, Xi; Xin, Guangyuan; Li, Xiaoyu
Abstract: The present study aimed to determine the chronic toxicity of 1-methyl-3-octylimidazolium bromide ([C8 mim]Br) on the silver carp to further reveal the toxicological mechanisms of ionic liquids. Chronic exposure of silver carp to [C8 mim]Br at concentrations of 1.095 and 4.380 mg/L for 60 d was conducted under laboratory conditions. The results revealed that chronic exposure to [C8 mim]Br inhibited the activity of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) and reduced glutathione (GSH) levels while markedly increasing malondialdehyde (MDA) and protein carbonyl (PC) levels in fish spleen, indicating that [C8 mim]Br treatment induced oxidative stress. Additionally, long-term exposure to [C8 mim]Br markedly upregulated the expressions of nuclear factor-κB (NF-κB), inducible nitric oxide synthase (iNOS), interleukin-1β (IL-1β), IL-6, tumour necrosis factor-α (TNF-α), and interferon-γ (IFN-γ); altered the levels of transforming growth factor-β (TGF-β); and increased the mRNA levels of p38MAPK, c-fos, c-jun, and c-myc, suggesting that long-term exposure to [C8 mim]Br might promote the inflammatory response in fish spleen and that p38MAPK/NF-κB signalling may potentially be involved in this process. Moreover, [C8 mim]Br-exposure altered lysozyme activity and complement 3 (C3) and immunoglobulin M (IgM) content, indicating that chronic [C8 mim]Br exposure also has immunotoxic effects on silver carp. Furthermore, we also found that [C8 mim]Br exposure reduced miR-125b levels, altered miR-143 levels, and upregulated miR-155 and miR-21 levels, suggesting that these miRNAs may be involved in the [C8 mim]Br-induced inflammatory response in fish spleen. In summary, the present study indicates that chronic exposure to [C8 mim]Br induces inflammation in fish spleen and that oxidative stress-mediated p38MAPK/NF-κB signalling and miRNAs may play a key role in this process. Highlights: Chronic exposure of [C8 mim]Br induced oxidative stress in silver carp spleen. Long-term exposure of [C8 mim]Br caused inflammatory reaction in fish spleen. p38MAPK/NF-κB were found to be involved in [C8 mim]Br-induced inflammation. microRNAs may play a pivotal role in [C8 mim]Br-caused inflammatory reaction.